Features Of Enzymatic Hydrolysis Of Fibers Of Genetically Different Cotton Lines - Nazarov K.K., Sagdiyev X.T., Kamolova Sh. (International Journal of Advanced Science and Technology, 2020)
The cont the a in c phys time, foun spec It wa rate. Key cotto study of biological factors affecting the process of enzymatic saccharification of cel aining substrates to di- and monosaccharides is an urgent task of modern biotechnology. reas of these studies is associated with the search for enzyme preparations that are most ef arrying out deep destruction of cellulose. Another thing — with the study of the influe ico-chemical properties and structure of cellulose on the course of bio conversion.For th the bio degradation processes of fibers of genetic varieties of cotton plants were studied. d that the effect of enzymes on the fibers of each variety of cotton was different. The su ificity of cellulases was determined with respect to the fibers of genetically different cotton s experimentally established that fibers of closely related lines undergo destruction at the